2003
DOI: 10.1002/jcu.10182
|View full text |Cite
|
Sign up to set email alerts
|

Chronic gastric volvulus and hypertrophic pyloric stenosis in an infant

Abstract: Chronic secondary mesenteroaxial gastric volvulus associated with hypertrophic pyloric stenosis has rarely been mentioned in the general medical literature. We report the case of a 2-month-old boy whose clinical symptoms, which included distension of the stomach and projectile vomiting, suggested the diagnosis of hypertrophic pyloric stenosis but who was later diagnosed with chronic secondary mesenteroaxial gastric volvulus. Sonographic examination revealed findings consistent with a rotated stomach, and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In a study of over 100 infants with HPS, Hernanz-Schulman et al found that robust overgrowth of the antral mucosa was responsible for obstruction of the pyloric opening51. Interestingly, a survey of the literature shows that HPS is often associated with other anomalies51, 52, including: abdominal malrotation or volvulus53, 54, cardiac anomalies55, imperforate anus, tracheal esophageal fistula56-58 and hydronephrosis of the kidney52, 59. Each of these malformations is seen in the VACTERL association, a constellation of abnormalities involving vertebral, anal, tracheal, esophageal, renal and limb development that are thought to be linked to defects in Hh signaling23.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of over 100 infants with HPS, Hernanz-Schulman et al found that robust overgrowth of the antral mucosa was responsible for obstruction of the pyloric opening51. Interestingly, a survey of the literature shows that HPS is often associated with other anomalies51, 52, including: abdominal malrotation or volvulus53, 54, cardiac anomalies55, imperforate anus, tracheal esophageal fistula56-58 and hydronephrosis of the kidney52, 59. Each of these malformations is seen in the VACTERL association, a constellation of abnormalities involving vertebral, anal, tracheal, esophageal, renal and limb development that are thought to be linked to defects in Hh signaling23.…”
Section: Discussionmentioning
confidence: 99%
“…A chronic gastric volvulus is probably more common than the acute presentation and is more commonly due to OA volvulus. Symptoms, which may include early satiety, intermittent dysphagia, failure to thrive, recurrent projectile vomiting, abdominal distention, GERD, colic, and sleep problems, 1 , 2 , 5 - 7 are harder to distinguish because they are similar to more typical conditions such as pyloric stenosis and reflux, 7 as was the case with our patient.…”
Section: Discussionmentioning
confidence: 52%
“…The short axis of the stomach joins the greater and lesser curvatures of the stomach ( Figure 2C ); rotation around this line suggests a mesenteroaxial volvulus (MA; Figure 2E ). 1 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…Generally, gastric distention, regardless of the cause, can cause rotation of the stomach in neonates and infants with lax or immature ligaments, with the possibility of gastric volvulus increased in patients with abnormal large amounts of subdiaphragmatic space [5]. Because the main symptoms of chronic gastric volvulus are recurrent projectile vomiting, abdominal distention, and failure to thrive overlap those of HPS, the differential diagnosis can be difficult [5].…”
Section: Case Reportmentioning
confidence: 99%
“…HPS has been found to be associated with certain malformations such as malrotation [4], chronic gastric volvulus [5,6], diaphragmatic eventration [5], diaphragmatic hernia [7], genitourinary tract abnormalities, and esophageal atresia [4,7].…”
Section: Introductionmentioning
confidence: 99%